2021
DOI: 10.3389/fbioe.2020.617034
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Potential of Rhizobium pusense MB-17a, a Plant Growth-Promoting Root Endophyte, and Functional Annotation of the Genes Involved in the Metabolic Pathway

Abstract: Plant growth-promoting rhizobacteria (PGPR) are root endophytic bacteria used for growth promotion, and they have broader applications in enhancing specific crop yield as a whole. In the present study, we have explored the potential of Rhizobium pusense MB-17a as an endophytic bacterium isolated from the roots of the mung bean (Vigna radiata) plant. Furthermore, this bacterium was sequenced and assembled to reveal its genomic potential associated with plant growth-promoting traits. Interestingly, the root endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…Positive effects of R. pusense GCB108 and GCB117 inoculation on growth of Raphanus sativus L. were comparable to prior investigations that demonstrated beneficial effects of Rhizobium as plant growth promoting bacteria in many plants including the non-legume plant radish [11]. It has been recently reported that the strain R. pusense MB-17a had all essential plant growth promoting traits based on biochemical tests and genomic evidence [7]. In this study, considerable increases in both shoot and root length of Raphanus sativus L. under hydroponic condition by R. pusense GCB108 and GCB117 inoculation suggest the high potential application of these two strains in biofertilizer production to stimulate growth of non-legume plants.…”
Section: Characteristics Of Rhizobium Pusense Gcb108 and Gcb117supporting
confidence: 76%
See 2 more Smart Citations
“…Positive effects of R. pusense GCB108 and GCB117 inoculation on growth of Raphanus sativus L. were comparable to prior investigations that demonstrated beneficial effects of Rhizobium as plant growth promoting bacteria in many plants including the non-legume plant radish [11]. It has been recently reported that the strain R. pusense MB-17a had all essential plant growth promoting traits based on biochemical tests and genomic evidence [7]. In this study, considerable increases in both shoot and root length of Raphanus sativus L. under hydroponic condition by R. pusense GCB108 and GCB117 inoculation suggest the high potential application of these two strains in biofertilizer production to stimulate growth of non-legume plants.…”
Section: Characteristics Of Rhizobium Pusense Gcb108 and Gcb117supporting
confidence: 76%
“…The results showed that the strains R. pusense GCB108 and GCB117 had the ability to produce catalase. Catalase is an important enzyme that helps bacteria protect their cells from oxidative stress and the ability of producing catalase has been well reported in many Rhizobium bacteria [7]. The ability of tolerance to salinity and different pH conditions is also important for microorganisms to be flexible in the environments.…”
Section: Characteristics Of Rhizobium Pusense Gcb108 and Gcb117mentioning
confidence: 99%
See 1 more Smart Citation
“…They exhibit chemolithotrophic growth in presence of inorganic sulfur. The heterotrophs include species of Achromobacter, Arthrobacter, Brevibacterium, Flavobacterium, Klebsiella, Micrococcus, Mycobacterium, Paracoccus, Streptomyces, Thiosphaera, and Xanthobacter (Wainwight, 1984;Kuenen et al, 1992, Ito et al, 2004Ryan et al, 2009;Sajjad et al, 2016;Chaudhary et al, 2017Chaudhary et al, , 2021. However, mixotrophs including species of Stenotrophomonas, Bacillus, Pseudomonas, Paenibacillus, Micrococcus, Pseudoclavibacter, Diaphorobacter, Aeromonas, Alcaligenes, Citrobacter, Rhizobium, and Bordetella are the key bacterial species playing important roles in nutrient mineralization and promoting plant growth (Sultan and Faisal, 2016;Sanwani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…pusense among others synthesizes IAA, thereby playing an important role in legume-rhizobia interaction [12][13][14][15][16][17] . It was reported that IAA acts as a signal molecule which is involved in plant signal processing, motility, or attachment of bacteria in root which help in legume-Rhizobium symbiosis 18 .…”
Section: Introductionmentioning
confidence: 99%